2016
DOI: 10.1016/j.socscimed.2015.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and older adults' sleep

Abstract: Sleep complaints are common among older adults, and poor sleep has been found to predict chronic diseases and mortality. Many studies suggest that social participation benefits healthy aging. We examined the relationships between older adults’ social participation and their sleep using two waves (2005–2006–2010–2011) of data from the National Social Life, Health, and Aging Project (NSHAP). The NSHAP recorded older adults’ social participation (including religious attendance, volunteer work, and attendance at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 65 publications
5
59
0
Order By: Relevance
“…It is widely believed that social participation is the key to healthy ageing. However, data from the US National Social Life, Health, and Aging Project has shown that older adults with greater social participation slept better, but increasing social participation did not improve sleep …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is widely believed that social participation is the key to healthy ageing. However, data from the US National Social Life, Health, and Aging Project has shown that older adults with greater social participation slept better, but increasing social participation did not improve sleep …”
Section: Introductionmentioning
confidence: 98%
“…However, data from the US National Social Life, Health, and Aging Project has shown that older adults with greater social participation slept better, but increasing social participation did not improve sleep. 8 The percentage of the elderly population is growing due to increased life expectancy and improved socioeconomic development. Surprisingly, in the World Health Organization's 2015 World Report on Ageing and Health, there is no mention of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Crosssectional analyses in a study published by Chen et al found positive associations between social participation and objectively-measured sleep among adults older than age 57. 21 No study to date has assessed the association between resilience and sleep in older adults. [21][22][23][24] Meanwhile, several studies have examined correlates of sleep complaints among older adults, but these efforts have not captured the full picture of physical and mental illness, medication use, and psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…21 No study to date has assessed the association between resilience and sleep in older adults. [21][22][23][24] Meanwhile, several studies have examined correlates of sleep complaints among older adults, but these efforts have not captured the full picture of physical and mental illness, medication use, and psychosocial factors. Thus, the primary objectives of this cross-sectional study were to (1) investigate the prevalence of poor sleep quality and short/long sleep duration among older adults with chronic musculoskeletal pain, and (2) estimate the effects of negative risk factors, medications, and positive psychosocial factors on these sleep outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies that focused on the link between SP and health measures relied on samples of old adults [7][8][9]. Only few focused on younger ages or examined the mediating role of different SP practices in the SES-health association [10,11].…”
Section: Introductionmentioning
confidence: 99%